Stability analysis of Takagi–Sugeno systems using a switched fuzzy Lyapunov function - Elias, Leandro J. (2021)
In this paper, a switched fuzzy Lyapunov function approach is proposed to analyze the stability of continuous-time Takagi–Sugeno fuzzy systems. The results are established by exploring properties of the membership functions. The key point is that the time derivatives of the membership functions are represented as a finite polytope and less conservative linear matrix inequalities are obtained. Numerical examples illustrate the efficiency of the new stabilizing conditions.